Effect of previous-day alcohol ingestion on muscle function and performance of severe-intensity exercise - Shaw, A. G.; Chae, S.; Levitt, D. E.; Nicholson, J. L.; Vingren, J. L.; Hill, D. W. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Many athletes report consuming alcohol the day before their event, which might negatively affect their performance. However, the effects of previous-day alcohol ingestion on performance are equivocal, in part, due to no standardization of alcohol dose in previous studies. The purpose of this study was to examine the impact of a standardized previous-day alcohol dose and its corresponding impact on morning-after muscular strength, muscular power, and muscular fatigue in a short-duration test and on performance of severe-intensity exercise.